2020
DOI: 10.1038/s41598-020-59736-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor as a new target for CAR-NK cell immunotherapy of triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC), representing ~15% of globally diagnosed breast cancer, is typically an incurable malignancy due to the lack of targetable surface targets for development of effective therapy. To address the unmet need for TNBC treatment, we recently determined that tissue factor (TF) is a useful surface target in 50-85% of patients with TNBC and developed a secondgeneration TF-targeting antibody-like immunoconjugate (called L-ICON) for preclinical treatment of TNBC. Using the chimeric ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 68 publications
0
91
0
1
Order By: Relevance
“…The results showed that fVII-targeted PDT was effective and selective in eradicating angiogenic VECs without harming normal VECs (Figure 5d-f) [83]. This study demonstrated the feasibility of fVII-conjugated photosensitizer as a method of targeting angiogenic VECs for PDT, supporting TF as an angiogenic-specific target in the PDT treatment of cancer [83] and AMD [105], as well as in ICON, L-ICON, and CAR-NK immunotherapy of pathological angiogenesis-dependent diseases, notably cancer [65,84,85,96,103,107], AMD [95,97], and endometriosis [94,98].…”
Section: Tissue Factor (Cd142)mentioning
confidence: 57%
See 2 more Smart Citations
“…The results showed that fVII-targeted PDT was effective and selective in eradicating angiogenic VECs without harming normal VECs (Figure 5d-f) [83]. This study demonstrated the feasibility of fVII-conjugated photosensitizer as a method of targeting angiogenic VECs for PDT, supporting TF as an angiogenic-specific target in the PDT treatment of cancer [83] and AMD [105], as well as in ICON, L-ICON, and CAR-NK immunotherapy of pathological angiogenesis-dependent diseases, notably cancer [65,84,85,96,103,107], AMD [95,97], and endometriosis [94,98].…”
Section: Tissue Factor (Cd142)mentioning
confidence: 57%
“…The Hu laboratory further improved the original ICON (with full length fVII) to L-ICONs (for fVII light chain ICON, to reduce its molecular weight and deplete residual procoagulation activity), called L-ICON1 (second generation) [65] and L-ICON3 (third generation; patent pending), for the treatment of TNBC with enhanced efficacy and safety profiles. Later, TF was also validated as a target in other cancer indications in others works investigating antibody-drug conjugates (ADC) against TF [100][101][102] and in our own work of chimeric antigen receptor-modified NK (CAR-NK) cell therapy [103] under preclinical and clinical investigations.…”
Section: Tissue Factor (Cd142)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they obtained CD16 + TF-CAR-NK cells, capable of mediating IgG1 and IgG3-mediated ADCC. The limitation of such strategy was the low transduction efficiency (~10%) [ 145 ]. The two-step transduction approach provided superior transduction efficiency (>90%) when used to generate ErbB2 and CD33 CAR-NK cells [ 129 ].…”
Section: Nk Cell Engineering Strategiesmentioning
confidence: 99%
“…Encouraging results have been reported in a phase I/IIa trial using cord blood-derived CAR-NK cells targeting CD19 in patients with relapsed or refractory non-Hodgkin's lymphoma and chronic lymphocytic leukemia, with up to 64% of patients achieving a complete response (93). In BC, tissue factor (TF) was recently described by Hu as a novel and common yet selective molecule on TNBC, whose targeting by TF-CAR NK cells resulted in an increased cytotoxicity against TNBC cell lines and was effective and safe for the treatment of TNBC in an orthotopic mouse model (94). Chen et al recapitulated these findings when investigating the effect of EGFR-CAR NK cells in TBNC cell lines and in mice preinoculated with brain metastases (95).…”
Section: Natural Killer (Nk) Cell Therapymentioning
confidence: 99%